2023
DOI: 10.3390/toxics11010049
|View full text |Cite
|
Sign up to set email alerts
|

Roe Deer (Capreolus capreolus) Hair as a Bioindicator for the Environmental Presence of Toxic and Trace Elements

Abstract: The return to pasture use as an alternative to intensive livestock farming implies some risks with the lack or the excessive presence of potentially toxic elements; in this regard, wild animals have been used as bioindicators for decades. Thus, the purpose of this study is quantifying Cu, Cr, Mn, Zn, Se, As, Cd, Ni, Pb, Al, Fe, and Mg in fur from roe deer and understanding if it is a valid bioindicator tool. Hair was collected from 39 hunted roe deer and divided by age (<36 months old/≥36 months old), sex (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Lead levels in devil hair, in both the validation study (mean 1.65 ± 4.61 SD) and the plantation landscape study (mean 1.05 ± 1.02 mg/kg), were comparable to other published research on lead exposure in mammals (both wild and domestic). The levels we found were lower than those found in the hair of domestic dogs ( Canis familiaris ) used for hunting in Argentina (mean 2.37 ± 6.21 mg/kg) (Fernández et al, 2021), similar to those in hair from fruit bats in eastern Australia (medians for three species: 1.26/1.64/2.26 mg/kg) (Sánchez et al, 2022) and roe deer in Italy (mean 1.39 ± 1.63 mg/kg) (Draghi et al, 2023), and higher than those found in hair from Malay civets sampled in Malaysian Borneo (mean 0.52 ± 1.08 mg/kg) (Evans et al, 2022). Similar to several of these studies (Draghi et al, 2023; Evans et al, 2022; Sánchez et al, 2022), there was no evidence of variations in lead levels in devil hair among sexes and age classes.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Lead levels in devil hair, in both the validation study (mean 1.65 ± 4.61 SD) and the plantation landscape study (mean 1.05 ± 1.02 mg/kg), were comparable to other published research on lead exposure in mammals (both wild and domestic). The levels we found were lower than those found in the hair of domestic dogs ( Canis familiaris ) used for hunting in Argentina (mean 2.37 ± 6.21 mg/kg) (Fernández et al, 2021), similar to those in hair from fruit bats in eastern Australia (medians for three species: 1.26/1.64/2.26 mg/kg) (Sánchez et al, 2022) and roe deer in Italy (mean 1.39 ± 1.63 mg/kg) (Draghi et al, 2023), and higher than those found in hair from Malay civets sampled in Malaysian Borneo (mean 0.52 ± 1.08 mg/kg) (Evans et al, 2022). Similar to several of these studies (Draghi et al, 2023; Evans et al, 2022; Sánchez et al, 2022), there was no evidence of variations in lead levels in devil hair among sexes and age classes.…”
Section: Discussionsupporting
confidence: 59%
“…One non-invasive approach to investigating heavy metal exposure in mammals is through hair analysis, a technique used by some recent studies on non-scavenging mammal species such as fruit bats ( Pteropus spp.) (Sánchez et al, 2022), Malay civets ( Viverra tangalunga ) (Evans et al, 2022) and roe deer ( Capreolus capreolus ) (Draghi et al, 2023). Collecting hair samples from wild animals can be done remotely using hair snares (Azad et al, 2019) or through minimal handling of trapped wild animals.…”
Section: Introductionmentioning
confidence: 99%
“…Different anthropogenic activities are responsible for the Al soil enrichment and consequent increase in the bioavailability of this compound in plants (45). In a study on roe deer hair (32), the animals that fed near urban areas had higher hair concentrations of Al than animals feeding in rural areas (32). In the same way, we could hypothesize that the difference in Al values before and after vertical transhumance could be due to the different origins of the feed.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between these studies could be explained not only by differences in the contamination of the regions due to anthropogenic activity, but also by differences in the geological characteristics of the areas. Indeed, As is naturally present in rocks and sediments [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our results, a study by Kasprzyk et al on the content of micro and macro elements in the liver of wild boars reported significant differences between sexes [ 58 ]. Also, in different studies on roe deer muscle, liver and hair, differences between the sexes in the contents of essential and non-essential elements were highlighted [ 37 , 59 ]. A possible explanation for the lack of statistically significant sex-related differences in our study is that, unlike the roe deer in other studies, whose females, due to the hunting season, could be in lactation or diapause, the female wild boars used in this study were neither pregnant nor lactating; these are physiological states that are known to greatly mobilize both essential and non-essential elements [ 60 ].…”
Section: Discussionmentioning
confidence: 99%